Ethylene signalling is essential for the resistance of Nicotiana attenuata against Alternaria alternata and phytoalexin scopoletin biosynthesis. (17th July 2016) - Sun, H.; Song, N.; Ma, L.; Li, J.; Ma, L.; Wu, J.; Wu, J.
Abstract : The phytohormone ethylene plays an important role in plant defence responses to pathogen attack. When infected by the necrotrophic fungal pathogen Alternaria alternata (tobacco pathotype), which causes severe diseases in Nicotiana species, the wild tobacco plant Nicotiana attenuata accumulates a high amount of the jasmonate (JA)‐dependent phytoalexin scopoletin to defend itself against this fungal pathogen. However, it is still not known whether ethylene signalling is also involved in scopoletin biosynthesis and the resistance of N. attenuata . After infection, ethylene biosynthetic genes were highly elicited. Furthermore, plants strongly impaired in ethylene biosynthesis or perception had dramatically decreased scopoletin levels, and these plants became more susceptible to the fungus, while A. alternata ‐elicited JA levels were increased, indicating that the decreased defence responses were not due to lower JA levels. Thus, it is concluded that after infection, ethylene signalling is activated together with JA signalling in N. attenuata plants and this subsequently regulates scopoletin biosynthesis and plant resistance.